PENGARUH MOTIVASI DAN DISIPLIN SERTA PENGALAMAN TERHADAP PRESTASI KERJA KARYAWAN AKADEMI MANAJEMEN INFORMATIKA DAN KOMPUTER DI KOTA PALEMBANG - Hendriansyah, - (Universitas muhammadiyah palembang, 2016)
This research test the influence of motivation and discipline and job experience toward employ achivement at the Academy of Computer and Information Management in Palembang. This research is implemented by regressing independent variables motivation, dicipline, and job experience toward dependent variables, job achievemen by using multiple regression model.The sample of this research consist of 42 respondents. The data is analized through deskriptif after converted into interval using method of succesive interval. Multiple linier regresi analisys was done by the assistant of SPSS for Windows to test the research hypotesis. The result of analisys cooeficient regression proved that motivation variabel, dicipline, job experience influenced significantly employees’ job achievement with constanta -0,342 motivation variabel influences significantly with coefisien regresion of 0,497 dicipline variabel with coefisien regresion of 0,375 and job experience also influence siganificantly with coefisien regresion of 0,216. The result of analisys using F test, the variable result F test of 17,484 was higher than F table with ? of 0,05 = 2,852 this means on the research with 0,05 significant error that there is significant influence of motivation, dicipline and job experience simultaneously toward job achievement at the academy of computer and information management employee in Palembang.